Management of congenital heart disease in the peripartum period: An illustrative case series - Cupido, Blanche (SA Heart Journal, 2022)
More women with complex congenital heart disease (CHD) reach adulthood resulting in a cohort of patients who are at high risk for adverse events during pregnancy. The haemodynamic changes usual to pregnancy may be poorly tolerated in patients with poor systemic ventricular function, cyanosis, left-sided obstructive lesions and pulmonary hypertension. Complex CHD patients are best managed by a multi-disciplinary team at a high-risk centre. Pre-conception counselling aims at risk stratifying by means of a clinical evaluation, electrocardiogram and echocardiography. Echocardiography plays a vital role in delineating the initial lesions and residual lesions with its haemodynamic complications. The modified WHO (mWHO) classification provides a helpful tool to stratify anatomical and physiological lesions by maternal and foetal event rates and is recommended by the European Society of Cardiology (ESC). Patients with cyanosis, severe aortopathy and severe pulmonary hypertension fall into Class IV and termination of pregnancy is advised. Patients may however choose to continue their pregnancy. We present 3 such cases of complex CHD (Fontan circulation, severe aortopathy and severe pulmonary hypertension) and illustrate some pertinent management principles in the peripartum period.